Development of Fiqh Learning Design Based on Ecotheological Integration and Digitalisation at MIN 4 Pontianak Timur - Sulpikar, Sulpikar; Wahab, Wahab (FiTUA: JURNAL STUDI ISLAM, 2026)
This study was motivated by the conventional, teacher-centred approach to teaching Fiqh, which has yet to integrate ecological awareness and optimal use of digital technology. The aim of the study was to develop a Fiqh teaching design based on eco-theological integration and digitalisation at MIN 4 Pontianak Timur that is relevant to the challenges of the 21st century. The research used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects included 44 fifth-grade students and three expert validators. The results of the study show that the developed learning design achieved a feasibility level of 80.21% from expert validation and a student response of 79.85%, including the categories ‘Feasible’ and ‘Good’. From the results of observations and tests, there was a proven increase in students' understanding of Fiqh concepts and the growth of environmental awareness. The novelty of this research lies in the systematic integration of eco-theological values with digital technology in Fiqh learning, creating more contextual and meaningful learning. The implications of this research provide practical contributions for Islamic Education teachers in designing innovative learning that develops students' cognitive, affective, and environmental awareness competencies holistically